Made A Thermostat With A 4 Axis Cnc Machining Process And Tooling Design - Kartikno, Jony; , Mr. Zou Yeas; , Wijianto, ST. M.Eng.Sc (2017)
Also known as the thermostat thermostat, coolant flow path control valve. As a thermostat device comprising temperature sensitive components generally, by expansion or shrink to open, turn off the flow of air, gas or liquid. Its role is automatically adjusted according to the level of the engine cooling water temperature of water entering the radiator, change the water cycle range for adjusting the cooling capacity of the cooling system to ensure the engine is operating at a suitable temperature range. Thermostat body itself cast aluminum alloy, five-sided machining body, processing contents, excellent air tightness requirements of the finished product, the relative processing requirements are relatively high. Processing thermostat body's need to use modern CNC machine tools, CNC machine tools development trend of modern high-speed, high-precision, high eliability, multi-functional, complex, intelligent and open chitecture. The main developments in the research and development of software and hardware with intelligent full-featured universal open architecture NC device. CNC machining technology is the basis for automation, CNC machine tools is the core technology, which is related to the level of national strategic position and reflects the level of comprehensive national strength. It is with the development of information technology, microelectronics technology, automation technology and detection techniques and development of. CNC machining center with a magazine and automatic tool change, the workpiece can be CNC machine tools, a variety of processing operations within a certain range.